The effect of curing temperature on the performance of thin film composite membrane - Idris, Ani; Kormin, Faridah; Mohd. Suput, Mohamad Zakiamani (Penerbit UTM Press, 2005)
The Effect Of Curing Temperature On The Performance Of Thin Film Composite Membranes Was Studied Using Two Different Kinds Of Polymeric Membrane Supports, I.E. Cellulose Acetate And Polysulfone. Aqueous Phase Solution Was Prepared By Dissolving M-Phenyldiamine, Tetrabutylammonium Bromide, Sodium Hydroxide And Hydroquinone Based On The Composition In Distilled Water. Organic Phase Was Prepared By Dissolving Trimesoyl Chloride In N-Hexane. Polymerization Occurred In The Organic Phase By Interfacial Reaction Of M-Phenyldiamine With The Presence Of Trimesoyl Chloride To Form Polyesteramides. Curing Temperatures Ranging From 40° To 100° C Were Used In The Air-Circulated Oven During The Interfacial Reaction Process. The Performances Of The Thin Film Composite Membranes In Terms Of Salt Rejection And Permeation Rate Were Evaluated Using The Permeation Cell. The Results Showed That Cellulose Acetate Thin Film Composite Membrane Cured At 60°C Gives The Best Rejection Rate Of 76% Whilst Polysulfone Thin Film Composite Membrane Cured At 80°C Gives The Highest Rejection Rate Of 80%.